Non-Genetic Factors Influencing Monthly Test Day Milk Yield Records In Murrah Buffaloes - Kumar, Abhishek; Gupta, Jay Prakash; Kaswan, Sandeep; Lathwal , S. S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Records for 10 Monthly test day milk yield (MTDMY) i.e. Test day milk yields (TDMY) at monthly interval (6th, 35th, 65th, 95th, 125th, 155th, 185th, 215th, 245th and 275th days) were collected from Murrah buffaloes maintained at cattle farm, National Dairy Research Institute, Karnal. These buffaloes were calved between the years 1996 to 2004 and completed three lactations. A total of 4,914 MTDMY records of 533 Murrah buffaloes were analyzed to study the effect of non-genetic factors (seasons and year of calving). The year of calving was having highly significant (P<0.01) influence on all MTDMYs (except 9th MTDMY), while season was having significant (P<0.05) effect only on 2nd MTDMY.